SPATIAL PLANNING IN SUPPORTING VILLAGE DEVELOPMENT - Meldi Rendra; Estananto Estananto (Charity : Jurnal Pengabdian Masyarakat, 2023)
Planning degrees have been focusing on rural studies, which make the best planning system for prevailing social welfare in villages. While village governments know development studies by demographic data in tabulation to evaluate/design the planning policies better or not. Different rural study models have been enriched and implemented in the past time. We use GIS to prove planning measures to be effective in rural governance to expand the decision-making process in planning policies. The participation/action research experienced a targeted planning policy in Covid 19 at Langensari-Lembang, Indonesia, found a method of static to dynamic, aggregated to disaggregated, and macro to micro. The results can visualize planning support in general solutions to specific adjustments of some public goods. Covid 19- suitable indicator schemes can design in isolated areas. Targets are how population aggregation and household mobilities in rural areas are affected by these planning policies. We believe action research improvements will employ a practical future on big data and artificial intelligence. Keyword: Spatial Planning, GIS, Decision Making